The high-entropy alloys with high hardness and soft magnetic property prepared by mechanical alloying and high-pressure sintering. (March 2016) - Yu, P.F.; Zhang, L.J.; Cheng, H.; Zhang, H.; Ma, M.Z.; Li, Y.C.; Li, G.; Liaw, P.K.; Liu, R.P.
Abstract: The equiatomic multiprincipal CoCrFeCuNi and CoCrFeMnNi high-entropy alloys (HEAs) were consolidated via high pressure sintering (HPS) from the powders prepared by the mechanical alloying method (MA). The structures of the MA'ed CoCrFeCuNi and CoCrFeMnNi powders consisted of a face-centered-cubic (FCC) phase and a minority body-centered cubic (BCC) phase. After being consolidated by HPS at 5 GPa, the structure of both HEAs transformed to a single FCC phase. The grain sizes of the HPS'ed CoCrFeCuNi and CoCrFeMnNi HEAs were about 100 nm. The alloys keep the FCC structure until the pressure reaches 31 GPa. The hardness of the HPS'ed CoCrFeCuNi and CoCrFeMnNi HEAs were 494 Hv and 587 Hv, respectively, much higher than their counterparts prepared by casting. Both alloys show typical paramagnetism, however, possessing different saturated magnetization. The mechanisms responsible for the observed influence of Cu and Mn on mechanical behavior and magnetic property of the HEAs are discussed in detail. Highlights: The CoCrFeCuNi and CoCrFeMnNi HEAs were synthesized by MA-HPS. The alloys keep FCC structure to 31 GPa demonstrated by synchrotron radiation. The HEAs show high hardness of 494 Hv and 587 Hv higher than the HEAs prepared by casting. The HEAs display different magnetic parameters for different alloying elements.